The Implementation of Authentic Assessment in Mathematics Learning to Improve Conceptual Understanding at SDN 03 Alai - Jendriadi, Jendriadi; Shoriah, Kamilah An; Putri, Rini Irmata; Ningsih, Fitria Dian; Fernanda, David (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Mathematics education in elementary schools is crucial for building a solid foundation of understanding that prepares students for more complex mathematical concepts in subsequent educational levels. However, traditional assessments, which often rely heavily on written exams, frequently fail to measure students' ability to think critically and apply mathematical concepts in real-world situations. This study aims to implement authentic assessment in mathematics learning at SDN 03 Alai to improve students' understanding and skills in applying mathematical concepts such as addition, subtraction, multiplication, division, and geometry in real-life contexts. The method used is Classroom Action Research (CAR) with cycles of planning, implementation, observation, and reflection. Data were collected through problem-based tests, observations, and student portfolios. The results show a significant improvement in students' understanding, with an average performance test score increasing by 22.6%, particularly in geometry (33.9%). This study recommends the broader implementation of authentic assessment in mathematics education to help students develop critical thinking and applied skills.